Investigating the Influence of Virtual Human Entourage Elements on Distance Judgments in Virtual Architectural Interiors - Aseeri, Sahar; Paraiso, Karla; Interrante, Victoria (Frontiers in Robotics and AI, 2019)
Architectural design drawings commonly include entourage elements: accessory objects, such as people, plants, furniture, etc., that can help to provide a sense of the scale of the depicted structure and "bring the drawings to life" by illustrating typical usage scenarios. In this paper, we describe two experiments that explore the extent to which adding a photo-realistic, three-dimensional model of a familiar person as an entourage element in a virtual architectural model might help to address the classical problem of distance underestimation in these environments. In our first experiment, we found no significant differences in participants' distance perception accuracy in a semi-realistic virtual hallway model in the presence of a static or animated figure of a familiar virtual human, compared to their perception of distances in a hallway model in which no virtual human appeared. In our second experiment, we found no significant differences in distance estimation accuracy in a virtual environment in the presence of a moderately larger-than-life or smaller-than-life virtual human entourage model than when a right-sized virtual human model was used. The results of these two experiments suggest that virtual human entourage has limited potential to influence peoples' sense of the scale of an indoor space, and that simply adding entourage, even including an exact-scale model of a familiar person, will not, on its own, directly evoke more accurate egocentric distance judgments in VR.